The relationship between children's media habits and their anxiety and behaviour during dental treatment. (3rd April 2018) - Jamali, Zahra; Vatandoost, Masoumeh; Erfanparast, Leila; Aminabadi, Naser Asl; Shirazi, Sajjad
Abstract: Objective: The existing evidence suggests that media habits may have moderating role on children's psychological adjustment in the dental setting. The aim of this study was to investigate the relationship between children's media habits and their anxiety and behaviour management problems (BMP) during dental treatment. Materials and methods: A total of 289 children aged 3–6 years old were included. Dental anxiety (DA) and BMP were assessed using Clinical Anxiety Rating Scale and Frankl's Rating Scale during the dental treatment. The parents reported their own DA, educational level and economic status; and the children's and also their own daily hours of using media. The data were analysed with the Mann–Whitney U, Kruskal–Wallis, Chi-square or Fisher exact tests, Spearman's correlation coefficient and logistic regression. Results: The children with DA had significantly higher amount of watching TV, playing e-games and surfing the Internet, and total amount of using electronic media than those without DA. The amount of watching TV and the total amount of using electronic media were significantly higher in the children with BMP than those without BMP. DA and BMP were significantly correlated with the children's hours of watching TV and total media time. Conclusions: There was a significant relationship between the amount of electronic media usage and DA and BMP in 3- to 6-year-old children.